Chinese Martial Arts Training Manuals: A Historical Survey - Monday, Nyle C. (Revista de Artes Marciales Asiáticas, 2012)
Brian Kennedy and Elizabeth Guo. Berkeley, CA: North Atlantic Books, 2005. 328 páginas. 15,2x20,3 cm. I.S.B.N.: 1-55643-557-6.